Modeling of constrained motion - Kleiza, Vytautas; Šatinskaitė, Rima (Lietuvos matematikos rinkinys, 2021)
This paper presents an investigation of modeling and solving of differential equations in the study of mechanical systems with holonomic constraints. The 2D and 3D mathematical models of constrained motion are made. The structure of the models consists of nonlinear first or second order differential equations. Cases of free movement and movement with resistance are investigated. Solutions of the Cauchy problem of obtained differential equations were obtained by Runge–Kutta method.
Keywords: mathematical model; nonlinear differential equation; constrained motion; gravitation force; energy dissipation